2012
DOI: 10.1007/s00429-012-0485-3
|View full text |Cite
|
Sign up to set email alerts
|

Regional gray matter density is associated with achievement motivation: evidence from voxel-based morphometry

Abstract: Achievement motivation can be defined as a recurrent need to improve one’s past performance. Despite previous functional imaging studies on motivation-related functional activation, the relationship between regional gray matter (rGM) morphology and achievement motivation has never been investigated. We used voxel-based morphometry and a questionnaire (achievement motivation scale) to measure individual achievement motivation and investigated the association between rGM density (rGMD) and achievement motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 77 publications
9
67
0
2
Order By: Relevance
“…2 Third, areas in the basal ganglia, orbitofrontal cortex and insula have various roles in reward and motivation processes. 34, 35 Interestingly, similar to psychostimulants, VGP causes substantial dopamine release in the dopaminergic system 5 and causes addiction. 6 Dopamine has been known to exhibit neurotoxic properties, and excessive dopamine damages tissues and cells in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…2 Third, areas in the basal ganglia, orbitofrontal cortex and insula have various roles in reward and motivation processes. 34, 35 Interestingly, similar to psychostimulants, VGP causes substantial dopamine release in the dopaminergic system 5 and causes addiction. 6 Dopamine has been known to exhibit neurotoxic properties, and excessive dopamine damages tissues and cells in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to structural imaging, gray matter density of the orbitofrontal cortex has also been associated with self-fulfillment achievement motivation in healthy individuals (Takeuchi et al 2014). In patients with schizophrenia, Venkatasubramanian et al (2008) found that lower left MOFC thickness was associated with higher negative symptom severity.…”
Section: Introductionmentioning
confidence: 99%
“…In food-rich environments, the long-term goal of weight control as a self-regulation process requires more cognitive resources than the proximal goal of food enjoyment does. There is evidence that both (i) proactive self-control efforts in response to immediate temptations and (ii) externally-imposed controls can help to protect long-term interests such as losing or maintaining weight (Takeuchi et al, 2014). However, it is plausible that weak self-control efforts and/or lack of responsiveness to external controls in response to immediate temptations impair one's ability to monitor or inhibit inappropriate behavior, consequently disrupting long-term weight control goals.…”
Section: Discussionmentioning
confidence: 99%
“…Following other published accounts (Ledberg et al, 1998; Takeuchi et al, 2014), in whole-brain analyses we used multiple linear regression analyses to identify regions in which regional gray matter volume (rGMV) was associated with RS scores. To control for possible confounding variables, BMI, age, gender and global GMV were entered as covariates within the regression model.…”
Section: Methodsmentioning
confidence: 99%